Pendampingan Identifikasi Potensi Wisata Desa Kalegen Dalam Mendukung Kawasan Agrowisata Umpak Sumbing - Maimunah Maimunah; Muhamad Taufan; Albertus Andhika Dewa Satria B.B; Marcell Pratama Bonantoro; Muhammad Sheva Nazera; Muhammad Wafiq Azizi (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The development of tourist villages is one of the government's efforts to improve the village economy and community welfare. BKAD Umpak Sumbing was formed to create the Umpak Sumbing agrotourism area in Bandongan District, Magelang Regency. Kalegen Village is one of the villages in the Umpak Sumbing area which has quite a lot of tourism potential in the form of nature tourism, fisheries and agriculture. There is a lot of tourism potential in Kalegen village that needs to be managed optimally. This community service activity assists in mapping superior tourism potential in Kalegen village to realize the development of the Umpak Sumbing agrotourism area. The results of identifying village tourism potential are expressed in digital mapping using QGIS software. Apart from that, to support the management of village tourism, it is necessary to optimize the Harapan Maju BUMDes by creating a BUMDes information system. Through the BUMDes information system, it is hoped that it can improve the performance of BUMDes